PENGARUH PERTUMBUHAN EKONOMI, INFLASI, KREDIT, DAN UANG ELEKTRONIK TERHADAP STABILITAS SISTEM KEUANGAN - Widyawati, Romya Seckar; Susilo (Contemporary Studies in Economic, Finance and Banking, 2024)
Unstable economic growth such as during the economic crisis and inequality in the financial inclusion system will have significant implications for financial system stability. Financial instability is characterized by a decline in public welfare, social instability, and broad economic losses. This study aims to examine the effect of economic growth, inflation, and financial inclusion on financial system stability. The analysis technique used is ECM. The dependent variable of financial system stability is measured by the Financial System Stability Index (ISSK) while the independent variables are economic growth, inflation, and the ratio of general banking credit to GDP and the volume of electronic money transactions to measure financial inclusion. The research data is secondary data with a quarterly period of 2012-2022. The empirical results of this study found that in the short term an increase in bank credit to GDP will increase stability. Meanwhile, an increase in economic growth, inflation, and the volume of electronic money transactions will reduce financial system stability.